Psychological Theory of Activity by A.N. Leontiev and Current Cognitive Studies - Vladislav A. Lektorsky (Lomonosov Moscow State University, 2023)
Background. In the year of Leontiev's 120th anniversary it is important to look again at his scientific heritage. Objective. The article aims to define the place of psychological theory of activity in the Soviet and Russian psychology and philosophy of the second half of the 20th century. Results. It is shown that Leontiev's theory predetermined a number of ideas of the intellectual movement 4E Cognition popular now in cognitive science. However, some important ideas of Leontiev are not yet utilized in modern cognitive research. The psychological theory of activity is compared with the concept of social constructionism in psychology, and in this respect the advantages of Leontiev's theory are revealed. Possible areas for further development of the psychological theory of activity are outlined. Conclusion. Leontiev's theory of activity thoroughly comprehends the problematics of activity, action, construction, and cultural-historical mediation of activity. This theory essentially defines the present of psychological science and makes it possible to outline a strategy for its future development.